2011
DOI: 10.1530/joe-10-0493
|View full text |Cite
|
Sign up to set email alerts
|

The effects of ACTH on steroid metabolomic profiles in human adrenal cells

Abstract: The adrenal glands are the primary source of mineralocorticoids, glucocorticoids and the so-called adrenal androgens. Under physiological conditions, cortisol and adrenal androgen synthesis are controlled primarily by adrenocorticotrophic hormone (ACTH). Although it is well established that ACTH can stimulate steroidogenesis in the human adrenal gland, the effect of ACTH on overall production of different classes of steroid hormones has not been defined. In this study, we examined the effect of ACTH on the pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
70
0
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 85 publications
(80 citation statements)
references
References 46 publications
(19 reference statements)
8
70
0
2
Order By: Relevance
“…LC-MS/MS analysis revealed that the most abundant unconjugated steroid hormones produced under basal conditions by the H295RA cells were 11-deoxycortisol, followed by androstenedione and cortisol. These results are consistent with previous LC-MS/MS steroid profiles reported in H295R cells (Xing et al 2011). The reasons for the relatively mild increase in cortisol after ACTH stimulation in our studies may relate to the low basal expression of CYP11B1 and slow ACTH-induction of the enzyme.…”
Section: Disscusionsupporting
confidence: 93%
See 3 more Smart Citations
“…LC-MS/MS analysis revealed that the most abundant unconjugated steroid hormones produced under basal conditions by the H295RA cells were 11-deoxycortisol, followed by androstenedione and cortisol. These results are consistent with previous LC-MS/MS steroid profiles reported in H295R cells (Xing et al 2011). The reasons for the relatively mild increase in cortisol after ACTH stimulation in our studies may relate to the low basal expression of CYP11B1 and slow ACTH-induction of the enzyme.…”
Section: Disscusionsupporting
confidence: 93%
“…Steroids produced by the H295R and H295RA cells at baseline and after ACTH stimulation are summarized in Table 2. Similar to our previous study of H295R steroid profiles (Xing et al 2011, Rege et al 2015, the main unconjugated steroids produced in H295RA cells were 11-deoxycortisol, androstenedione, and cortisol, while the mass of aldosterone was low under basal conditions. After ACTH stimulation for 24 h, H295RA cells showed a significant increase in 17a-hydroxyprogesterone, 11-deoxycorticosterone, corticosterone, 11-deoxycortisol, pregnenolone sulfate, and 17a-hydroxypregnenolone sulfate as well as aldosterone and cortisol (P!0.05; Table 2).…”
Section: Steroidogenic Ability Of the H295ra Cell Linesupporting
confidence: 87%
See 2 more Smart Citations
“…Moreover, adrenocorticotropic hormone regulates adrenal production of cortisol in the zona fasciculata and of androgenic steroids (i.e. dehydroepiandrosterone and ADD) in the zona reticularis (Schimmer and Funder, 2011;Xing et al, 2011), a phenomenon constituting another similarity between the two classes of steroids.…”
Section: Introductionmentioning
confidence: 99%